Changes in the personality profile of young women with latent toxoplasmosis - Flegr, J; Havlícek, J (Folia parasitologica, 1999)
Latent toxoplasmosis is the most widespread parasite infection in developed and developing countries. The prevalence of Toxoplasma gondii infection varies mostly between 20 to 80% in different territories. This form of toxoplasmosis is generally considered to be asymptomatic. Recently published results, however, suggest that the personality profiles of infected subjects differ from those of uninfected controls. These results, however, were obtained on non-standard populations (biologists or former acute toxoplasmosis patients). Here we studied the personality profiles of 191 young women tested for anti-Toxoplasma immunity during gravidity. The results showed that the differences between Toxoplasma-negative and Toxoplasma-positive subjects exits also in this sample of healthy women. The subjects with latent toxoplasmosis had higher intelligence, lower guilt proneness, and possibly also higher ergic tension. The difference in several other factors (desurgency/surgency, alaxia/protension, naiveté/shrewdness, and self-sentiment integration) concerned changes in the variances, rather than the mean values of the factors.
Keywords: Pregnancy; Humans; toxoplazmóza; parazitární komplikace těhotenství; Personality Inventory; osobnostní dotazník; Female; Toxoplasmosis; dospělí; komplement fixační testy; lidé; zvířata; Adult; ženské pohlaví; Toxoplasma; Adolescent; protilátky protozoální; těhotenství; osobnost; Antibodies, Protozoan; Animals; Personality; Pregnancy Complications, Parasitic; Complement Fixation Tests; mladiství